Optimalisasi Peran Perawat dalam Penerapan Atraumatic Care di Ruang Perawatan Anak - Hermalinda Herman; Lili Fajria; Deswita Nurshal; Yanti Puspita Sari; Dwi Novrianda; Ira Mulya Sari; Yelli Herien; Arif Rahman Mansyur (Warta Pengabdian Andalas, 2019)
Atraumatic care as a form of therapeutic care is provided to children and families by reducing the psychological impact of nursing actions offered. The problem is the application of the principle of atraumatic care in a pediatric ward of Unand's Hospital. The problem is due to the limited number of nurses and the lack of experience of nurses, especially in caring for children. Based on these problems, the alternative of problem-solving conduct seminars and workshops on nurses about optimizing the role of nurses in the application of atraumatic care in the pediatric ward. The purpose of these activities is to improve the knowledge and skill of nurses in applying atraumatic care in a pediatric department. The place of community services is in Andalas University Hospital Padang. Community service activities are carried out starting from the preparation stage, the implementation stage (training and outreach), the monitoring and evaluation phase. Methods of carrying out activities with lectures, focus group discussions (FGD), role play, and individual learning. The result of the action is an increase in nurses' knowledge and skills regarding the application of atraumatic care in the childcare room. It is expected that the hospital can carry out refreshment activities on an ongoing basis to improve the quality of child nursing care.